Human Acellular Dermis as Spacer for Small-Joint Arthroplasty: Analysis of Revascularization in a Rabbit Trapeziectomy Model. Issue 3 (September 2018) - Banks, Kian; Squitieri, Lee; Bramos, Athanasios; Johnson, Maxwell B.; Gardner, Daniel J.; Pourmoussa, Austin J.; Jung, Eunson; Lee, Gene K.; Perrault, David P.; Fedenko, Alexander; Kim, Gene H.; Han, Bo; et al.
Abstract : Background: Carpometacarpal joint osteoarthritis affects 8 to 12 percent of the general population. Surgical management provides symptomatic relief for 78 percent of patients who fail conservative therapy, but little consensus exists regarding which surgical procedure provides superior patient outcomes. Recent human trials substituted exogenous acellular dermal matrices in the bone space, but there are no quantitative histologic data on the outcome of acellular dermal matrices in this environment. The authors aimed to quantify the revascularization and recellularization of acellular dermal matrices in the joint space using a rabbit model. Methods: Bilateral lunate carpal bones were surgically removed in New Zealand rabbits. Acellular dermal matrix and autologous tissue were implanted in place of the lunate of the right and left wrists, respectively. Acellular dermal matrix was also implanted subcutaneously as a nonjoint control. Histologic and immunofluorescence analysis was performed after collection at 0, 6, and 12 weeks. Results: Quantitative analysis of anti–α-smooth muscle actin and CD31 immunofluorescence revealed a sequential and comparable increase of vascular lumens in joint space and subcutaneous acellular dermal matrices. In contrast, autologous tissue implanted in the joint space did not have a similar increase in α-smooth muscle actin–positive or CD31-positive lumens. Semiquantitative analysis revealed increased cellularity in both autologous and acellular dermal matrix wrist implants at each time point, whereas average cellularity of subcutaneous acellular dermal matrix peaked at 6 weeks and regressed by 12 weeks. Trichrome and Sirius red staining revealed abundant collagen at all time points. Conclusion: The trapeziectomy joint space supports both cellular and vascular ingrowth into human acellular dermal matrix.